SPE Improved Oil Recovery Conference 2016
DOI: 10.2118/179589-ms
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Permeability Reduction of Water-Soluble Silicate Gelants - Importance of Formation Wettability

Abstract: Disproportionate permeability reduction (DPR) may provide field solutions to address high volumes of water production and efficiency of oil recovery in non-communicating layered reservoirs. This work evaluates the lab-scale DPR effectiveness at different formation wettability conditions using an environmentally friendly, water-soluble, silicate gelant. A robust, time/temperature stable and easy-to-design water-soluble silicate gelant system is utilized to conduct DPR treatments in oil-and water-wet cores using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In other words, the RPM's swelling/shrinking characteristics depend on the flowing fluid phase that ultimately leads to DPR phenomena and aids in selective permeability reduction (SPR). [26][27][28][29]41,111,161,178,179,181,185,192,193 The factors that influence the RPM's swelling/shrinking phenomena are the following:…”
Section: Lubrication Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the RPM's swelling/shrinking characteristics depend on the flowing fluid phase that ultimately leads to DPR phenomena and aids in selective permeability reduction (SPR). [26][27][28][29]41,111,161,178,179,181,185,192,193 The factors that influence the RPM's swelling/shrinking phenomena are the following:…”
Section: Lubrication Effectsmentioning
confidence: 99%
“…Type of Flowing Fluid (Water, Oil, or Gas). It has been reported that as water can defuse through the polymer/ gel layer, the water induces charge repulsion between the hydrolyzed groups in polymer/gel which in turn the polymer/ gel swells and subsequently resists the flow of water; 27,37,41,111,181,185,192 see Figure 14a. Furthermore, it has been stated that the mechanical force exerted by flowing oil/ gas fluid on polymer/gel causes water expulsion from the polymer/gel which eventually causes gel shrinkage; 22,23,30,33,41,45,46,111,160,181,182,185,194 see Figure 14b.…”
Section: Lubrication Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a strong water-wet rock, the relative permeability curves will crossover at a wetting phase saturation point of greater than 0.5, while a strong oil-wet rock relative permeability curves will crossover at a wetting phase saturation point of lesser than 0.5. A crossover point at a saturation of 0.5 and equal end points of relative permeability curve imply that the reservoir rock is in neutral-wet condition [16].…”
Section: Concept Of Wettabilitymentioning
confidence: 99%
“…Berea core samples are chemically treated to alter their wettability towards oil-wet (oil-wet or less water-wet depending on the treatment procedure). A summary of the wettability alteration process together with the wettability characterization of oil-wet cores are presented by Askarinezhad et al (2017a). The measured cores porosity and absolute brine permeability values are in the range of 21% -23% and 500 mD -900 mD, respectively.…”
Section: Rock and Fluids -Preparation And Characterizationmentioning
confidence: 99%